Comparison of Nineteen Chemical Element Contents in Normal Thyroid and Thyroid with Riedel’s Struma - Zaichick, Vladimir (Jour Med Resh and Health Sci, 2021)
Background: Role of chemical elements (ChE) in etiology and pathogenesis of Riedel’s disease (RD) is unclear. Objectives: The aim of this exploratory study was to assess whether there were significant changes in thyroid tissue levels of nineteen ChE (Ag, Br, Ca, Cl, Co, Cr, Fe, Hg, I, K, Mg, Mn, Na, Rb, Sb, Sc, Se, Sr, and Zn) are present in the fibrotic transformed thyroid. Methods: Nineteen ChE of thyroid tissue were determined in 6 patients with RD. The control group included thyroid tissue samples from 105 healthy individuals. Measurements were conducted using combination of non-destructive methods such as energy dispersive X-ray fluorescent analysis and instrumental neutron activation analysis. Results: Reduced mean values of Ca and I content in 6.3 and 6.7 times, respectively, while elevated level of Br and Rb in 5.9 and 1.9 times, respectively, were found in thyroid with RD in comparison with normal level. Conclusions: There are considerable changes in some ChE contents in tissue of thyroid with RD. Thus, it is reasonable to assume that the levels of these ChE in affected thyroid tissue can be used as RD markers. However, this topic needs additional studies.